Basic landing characteristics and their application in artistic gymnastics - Marinsek, M. (Science of Gymnastics Journal, 2010)
Landings are extremely important in gymnastics to improve athlete performances as well as to reduce injuries. Studies on landings therefore provide an interesting field of research in which numerous studies have been conducted. This article gives an overview of the results from these studies that can be used by coaches to improve teaching on landing techniques. The biomechanical characteristics and motor control of landings is reviewed.